Population exposure to pre-emptive de-energization aimed at averting wildfires in Northern California - Abatzoglou, John T; Smith, Craig M; Swain, Daniel L; Ptak, Thomas; Kolden, Crystal A (Environmental research letters, 2020)
Recent extreme fire seasons in California have prompted utilities such as Pacific Gas and Electric to pre-emptively de-energize portions of the electrical grid during periods of extreme fire weather to reduce the risk of powerline-related fire ignitions. The policy was deployed in 2019, resulting in 12 million person-days of power outages and widespread societal disruption. Retrospective weather and vegetation moisture data highlight hotspots of historical risk across northern California. We estimate an average of 1.6 million person-days of de-energization per year, based on recent historical climate conditions and assuming publicly stated utility de-energization thresholds. We further estimate an additional 70% increase in the population affected by de-energization when vegetation remains abnormally dry later into autumn-suggesting that climate change will likely increase population vulnerable to de-energization. Adaptation efforts to curtail fire risk can be beneficial, but efforts to prepare affected populations, modernize the grid, and refine decision-making surrounding such policies have high potential to reduce the magnitude of negative externalities experienced during the 2019 de-energization events.